(3cJGH ajeG jLH deJYGWi GdMQhHs
(3ChdgG (B:s
(3GdMeO ddg eYdi QJHI ef EJUa HGdTLGYI hHYO aEf ddMQH dhGRe dGjSJZfi YfgG , hLhGRe dGHO ddeJUa HGdTLGYI efgG hbO VefG gPG GdcJGH eG jLH deJYGWi GdMQH s
(3BNQgG (B:s
(3GdHGH GdKdGKhf ai GdefGUH GdMQHjI EPG hjQei GdaGQS ef Ydi XgQg hGddg Gdehab ddUhGH hUdi Gddg Ydi SjOfG eMeO hBdg hUMHg hSde JSdjekG cKjQkG Edi jhe GdOjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3ai KdGKjf HGHkGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3Gdafhf GdMQHjI h GdaQhSjIs